2006
DOI: 10.1093/hmg/ddl223
|View full text |Cite
|
Sign up to set email alerts
|

Heterogeneity at the HLA-DRB1 locus and risk for multiple sclerosis

Abstract: Variation in major histocompatibility complex genes on chromosome 6p21.3, specifically the human leukocyte antigen HLA-DR2 or DRB1*1501-DQB1*0602 extended haplotype, confers risk for multiple sclerosis (MS). Previous studies of DRB1 variation and both MS susceptibility and phenotypic expression have lacked statistical power to detect modest genotypic influences, and have demonstrated conflicting results. Results derived from analyses of 1339 MS families indicate DRB1 variation influences MS susceptibility in a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

14
261
8
6

Year Published

2007
2007
2016
2016

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 282 publications
(289 citation statements)
references
References 60 publications
14
261
8
6
Order By: Relevance
“…Variation in the MHC, specifically the HLA-DRB1*15 haplotype, is the strongest known genetic factor for MS, and results from multiple studies support this association. 32,33 The complex contribution from this region, however, is estimated to account for only a portion of the risk for the disease. On the basis of these results, it is clear that common (frequency 45 to 10%) non-MHC MS susceptibility alleles confer quite modest risk (odd ratios o2), and are difficult to detect using linkage studies.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Variation in the MHC, specifically the HLA-DRB1*15 haplotype, is the strongest known genetic factor for MS, and results from multiple studies support this association. 32,33 The complex contribution from this region, however, is estimated to account for only a portion of the risk for the disease. On the basis of these results, it is clear that common (frequency 45 to 10%) non-MHC MS susceptibility alleles confer quite modest risk (odd ratios o2), and are difficult to detect using linkage studies.…”
Section: Discussionmentioning
confidence: 99%
“…20 The diagnostic criteria, ascertainment protocols and clinical and demographic characteristics of these populations are described in more detail elsewhere. 31,32,36,45 The EDSS 46 was used in conjunction with disease duration to define very mild or severe forms of MS as a secondary phenotype for analysis, as previously described. 32 Disease duration was measured as the number of years between the year of onset of first symptom and year of last exam with EDSS assessment; in most cases this is at the entry of the study, given the cross-sectional nature of these datasets.…”
Section: Methodsmentioning
confidence: 99%
“…The strongest susceptibility signal maps to the HLA-DRB1 gene in the class II region of the major histocompatibility complex (MHC) (Barcellos et al, 2006;Yeo et al, 2007). Recently, the two largest genome-wide association studies (GWAS) of MS genetics confirmed HLA as the major MS susceptibility locus and provided unequivocal evidence for the association of additional 110 non-MHC "candidate" genetic variants conferring susceptibility to the disease (IMSGC, 2011;IMSGC, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…The risk haplotype that has been identified for the Caucasian populations is HLA DRB1*1501-DQB1*0602 (also known as DR15 haplotype) in the HLA-class II region. In the Italian 3 as well as in other European populations, [4][5][6] DR15 confers an odds ratio (OR) of about 3.…”
Section: Introductionmentioning
confidence: 99%